Spirit of Balinese Local Heroes Transformed into Puppets Show on YouTube as ELT Media for Building Students' Character - I Putu Yoga Purandina; Kadek Adyatna Wedananta (Universitas Pendidikan Ganesha, 2021)
Balinese Local Heroes should be role models for all children around Bali. The spirit of the heroes is full of positive characters. Those characters are essential in building a good personality in every single kid. This study aims to analyze Balinese local heroes' effect into puppets show on Youtube as ELT media for building students' character. The research was designed as a qualitative study. The data taken from the observed interaction at the puppets showed on YouTube that students watched. The obtained data were students' and parent's data interviews and questionnaires. The study results showed that Balinese Local Heroes' spirit transformed into puppet shows on YouTube affected students accurately because the media was engaging. Some character values were affected, willingness to sacrifice, bravery, defense of truth and justice, noble, responsible, and patriotic. The social function of all of the values was essential. The values transformed into a positive attitude in social life. The student became a good helper to the people who need help. They clean the environment without any intention and have a responsibility to do their duty as a student.